Anti-CTLA4 treatment reduces lymphedema risk potentially through a systemic expansion of the FOXP3+ Treg population - Wolf, Stefan; Madanchi, Matiar; Turko, Patrick; Hollmén, Maija; Tugues, Sonia; von Atzigen, Julia; Giovanoli, Pietro; Dummer, Reinhard; Lindenblatt, Nicole; Halin, Cornelia; Detmar, Michael; Levesque, Mitchell; et al. (NATURE PORTFOLIO, 2025)
Secondary lymphedema is a common sequel of oncologic surgery and presents a global health burden still lacking pharmacological treatment. The infiltration of the lymphedematous extremities with CD4+T cells influences lymphedema onset and emerges as a promising therapy target. Here, we show that the modulation of CD4+FOXP3+CD25+regulatory T (Treg) cells upon anti-CTLA4 treatment protects against lymphedema development in patients with melanoma and in a mouse lymphedema model. A retrospective evaluation of a melanoma patient registry reveals that anti-CTLA4 reduces lymphedema risk; in parallel, anti-CTLA4 reduces edema and improves lymphatic function in a mouse-tail lymphedema model. This protective effect of anti-CTLA4 correlates with a systemic expansion of Tregs, both in the animal model and in patients with melanoma. Our data thus show that anti-CTLA4 with its lymphedema-protective and anti-tumor properties is a promising candidate for more diverse application in the clinics.